Causal relationship between gut microbiota and puerperal sepsis: a 2-sample Mendelian randomization study - Liang, Liu-dan; Li, Sheng; Huang, Mei-jin; Peng, Hui-xin; Lu, Zi-jun; Zhang, Zhuo-hua; Su, Li-ye; Sooranna, Suren R.; Liu, Yan; Huang, Zhao-he (Frontiers in Microbiology, 2024)
Background Some recent observational studies have shown that gut microbiota composition is associated with puerperal sepsis (PS) and no causal effect have been attributed to this. The aim of this study was to determine a causal association between gut microbiota and PS by using a two-sample Mendelian randomization (MR) analysis. Methods This study performed MR analysis on the publicly accessible genome-wide association study (GWAS) summary level data in order to explore the causal effects between gut microbiota and PS. Gut microbiota GWAS (n = 18,340) were obtained from the MiBioGen study and GWAS-summary-level data for PS were obtained from the UK Biobank (PS, 3,940 cases; controls, 202,267 cases). Identification of single nucleotide polymorphisms associated with each feature were identified based on a significance threshold of p < 1.0 × 10–5. The inverse variance weighted (IVW) parameter was used as the primary method for MR and it was supplemented by other methods. Additionally, a set of sensitivity analytical methods, including the MR-Egger intercept, Mendelian randomized polymorphism residual and outlier, Cochran’s Q and the leave-one-out tests were carried out to assess the robustness of our findings. Results Our study found 3 species of gut microbiota, Lachnospiraceae FCS020, Lachnospiraceae NK4A136, and Ruminococcaceae NK4A214, to be associated with PS. The IVW method indicated an approximately 19% decreased risk of PS per standard deviation increase with Lachnospiraceae FCS020 (OR = 0.81; 95% CI 0.66–1.00, p = 0.047). A similar trend was also found with Lachnospiraceae NK4A136 (OR = 0.80; 95% CI 0.66–0.97, p = 0.024). However, Ruminococcaceae NK4A214 was positively associated with the risk of PS (OR = 1.33, 95% CI: 1.07–1.67, p = 0.011). Conclusion This two-sample MR study firstly found suggestive evidence of beneficial and detrimental causal associations of gut microbiota on the risk of PS. This may provide valuable insights into the pathogenesis of microbiota-mediated PS and potential strategies for its prevention and treatment.